Public Health Climate Change Adaptation Planning Using Stakeholder Feedback. (January 2016) - Eidson, Millicent; Clancy, Kathleen A.; Birkhead, Guthrie S.
Abstract : Context: Public health climate change adaptation planning is an urgent priority requiring stakeholder feedback. The 10 Essential Public Health Services can be applied to adaptation activities. Objective: To develop a state health department climate and health adaptation plan as informed by stakeholder feedback. Design: With Centers for Disease Control and Prevention (CDC) funding, the New York State Department of Health (NYSDOH) implemented a 2010-2013 climate and health planning process, including 7 surveys on perceptions and adaptation priorities. Participants: New York State Department of Health program managers participated in initial (n = 41, denominator unknown) and follow-up (72.2%) needs assessments. Surveillance system information was collected from 98.1% of surveillance system managers. For adaptation prioritization surveys, participants included 75.4% of NYSDOH leaders; 60.3% of local health departments (LHDs); and 53.7% of other stakeholders representing environmental, governmental, health, community, policy, academic, and business organizations. Interviews were also completed with 38.9% of other stakeholders. Results: In 2011 surveys, 34.1% of state health program directors believed that climate change would impact their program priorities. However, 84.6% of state health surveillance system managers provided ideas for using databases for climate and health monitoring/surveillance. In 2012 surveys, 46.5% of state health leaders agreed they had sufficient information about climate and health compared to 17.1% of LHDs ( P = .0046) and 40.9% of other stakeholders (nonsignificant difference). Significantly fewer ( P < .0001) LHDs (22.9%) were incorporating or considering incorporating climate and health into planning compared to state health leaders (55.8%) and other stakeholders (68.2%). Stakeholder groups agreed on the 4 highest priority adaptation categories including core public health activities such as surveillance, coordination/collaboration, education, and policy development. Conclusions: Feedback from diverse stakeholders was utilized by NYSDOH to develop its Climate and Health Strategic Map in 2013. The CDC Building Resilience Against Climate Effects (BRACE) framework and funding provides a collaborative model for state climate and health adaptation planning. Abstract : Supplemental Digital Content is Available in the Text.The objective of this study was to develop a state health department climate and health adaptation plan as informed by stakeholder feedback.